Build it, fix it, own it : a beginner's guide to building and upgrading a PC - McFedries, Paul (Que, 2008)
A guide to building, repairing, and upgrading a PC offers explanations of concepts, along with instructions on how to build a PC, covering the essential parts of a PC and explaining how hardware works, types of hardware available, and how to build and maintain five different PC types.